Análise do comportamento hidráulico da caixa de transição de sistemaextravasor em encosta por meio de modelo hidráulico reduzido - Larissa Soares Carvalho (2016)
The use of physical modeling for the development of engineering projects aims to predict the prototype's behavior from observations made in its model. The physical modeling techniques are based on the similarity of these two systems, considering that observations taken in the model are easier and less costly to obtain, and changing model conditions as well. The following study presented is about the design of a dam spillway operating system, from Forquilha IV, for which it was necessary the construction of a reduced physical model (geometrical scale 1:10) due to the singularity and the complexity of the hydraulic structure. The objective of this study is to compare theoretical results with the values obtained in the tests performed in laboratory with regard to the characteristics of the hydraulic jump developed in the dissipation box along with the consequences of silting in the box. The purpose of the latter is to assess the need for cleaning the box supposing eventualsedimentation that might be caused by an extreme event or some problem in the spillway operation system, knowing the difficulty of maintenance and cleaning of the box. The experimental results indicated that the spillway operating system designed has the means to runoff the tested flows safely, even though it was not possible for some to achieve the complete development of the hydraulic jump along the transition box. The tests on the silted box showed that the design flow is capable of carrying entirely materials with similar characteristics to tailings of iron ore.